Optimizing paediatric eye health with Homeopathy: A review - Kotian, Shreyank; Noronha, Reshel (Indian Journal of Integrative Medicine, 2023)
The equilibrium of sensory organs has consistently been crucial for the holistic growth and development of a child. Among these, the significance of the eyes and vision has been paramount in shaping a child’s progress. As the child matures, maintaining optimal eye health and vision has a direct correlation with their ability to keep pace in today’s fast-paced world. But after the COVID-19 pandemic, the reliance on digital platforms for educational and recreational purposes among children has become nearly unavoidable. Consequently, there is a growing apprehension regarding the impact on children’s eye health, necessitating a deeper exploration of the underlying causes of these eye-related issues. This article aims to introduce and explore eye and vision conditions that impact pediatric individuals, ranging from neonates to adolescents. Through the compilation of information from diverse published articles indexed in Google Scholar and PubMed, as well as standard Homoeopathic literature, a concise review is presented on various ophthalmological conditions. The primary objective is to provide insights into the approach of Homoeopathy in addressing these conditions and offer a comprehensive overview of the subject.